Assessment of Chemical, Physicochemical, and Lipid Stability Properties of Gelled Emulsions Elaborated with Different Oils Chia (Salvia hispanica L.) or Hemp (Cannabis sativa L.) and Pseudocereals - Botella-Martínez, Carmen (Foods, 2021)
Gelled emulsion (GE) systems are one of the novel proposals for the reformulation of meat products with healthier profiles. The aims of this research were (i) to develop gelled emulsions using pseudocereal flours (amaranth, buckwheat, teff, and quinoa) and vegetable oils (chia oil, hemp oil, and their combination), (ii) to determine their chemical composition, physicochemical properties, and lipid stability, and (iii) to evaluate their stability during frozen storage. The results showed that GEs are technologically viable except for the sample elaborated with teff flour and a mix of oils. The lipid oxidation was not greater than 2.5 mg malonaldehyde/kg of sample for any of the samples analyzed. The physicochemical properties analyzed showed both the pH and color values of the GEs within the range of values obtained for the fat of animal origin. The texture properties were affected by the type of oil added; in general, the firmness and the work of shear increased with the addition of the mixture of both oils. The samples elaborated with buckwheat and chia oil and quinoa and chia oil had the highest emulsion stability values, which remained among the highest after freezing. The results showed that gelled emulsions, based on chia oil, hemp, and their mixture with pseudocereal flours, are a viable alternative as a possible substitute of saturated fat in the development of novel foods.